2012
DOI: 10.1097/gme.0b013e318248f50f
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lifestyle interventions in dynapenic-obese postmenopausal women

Abstract: Our results suggest that CR with or without RT is effective in improving metabolic profile, whereas RT is effective in improving physical capacity. The combination of RT and CR may be particularly relevant in maximizing improvements in physical capacity in dynapenic-obese postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 52 publications
1
17
0
1
Order By: Relevance
“…In 21 sarcopenic obese adults aged 60 years or older randomised to 15 weeks of strength/hypertrophy or high speed (power) circuit training, no differences were observed for changes in body fat and physical performance, but lower-limb power tended to improve more for the circuit training group [80]. In a factorial design RCT involving 38 postmenopausal women with dynapenic obesity randomised to either 12-weeks of PRT, caloric restriction, both or a control group, caloric restriction alone or in combination with PRT was associated with an improvement in body weight, fat mass and cardiometabolic health while PRT had a beneficial effect on physical performance [81]. The findings from these small trials are supportive of the concept that multimodal exercise interventions incorporating PRT and combined with caloric restriction are effective therapies for sarcopenic and dynapenic obesity.…”
Section: Exercisementioning
confidence: 70%
“…In 21 sarcopenic obese adults aged 60 years or older randomised to 15 weeks of strength/hypertrophy or high speed (power) circuit training, no differences were observed for changes in body fat and physical performance, but lower-limb power tended to improve more for the circuit training group [80]. In a factorial design RCT involving 38 postmenopausal women with dynapenic obesity randomised to either 12-weeks of PRT, caloric restriction, both or a control group, caloric restriction alone or in combination with PRT was associated with an improvement in body weight, fat mass and cardiometabolic health while PRT had a beneficial effect on physical performance [81]. The findings from these small trials are supportive of the concept that multimodal exercise interventions incorporating PRT and combined with caloric restriction are effective therapies for sarcopenic and dynapenic obesity.…”
Section: Exercisementioning
confidence: 70%
“…However, the role of RT volume on fat loss in PW is not clear. The RT protocol used to promote hypertrophy has shown modest to no effect on indicators of body fat and metabolic risk in PW (Brochu et al 2009;Lera Orsatti et al 2014;Maesta et al 2007;Phillips et al 2012;Senechal et al 2012), and there are no studies that have used more than three sets on indicators of body fat and metabolic risk in PW. Studies using acute resistance exercise have shown that higher RT volume is associated with higherenergy expenditure (Haddock and Wilkin 2006;Phillips and Ziuraitis 2004) and with greater activation of signaling pathways that regulate PGC-1α (Ahtiainen et al 2015;Combes et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The American College of Sports Medicine (ACSM) recommends resistance training (RT; two to three times a week, eight to ten exercises, and one to three sets of 8-15 repetitions at 60-80 % of one repetition maximum) to improve muscular mass and strength and avoid sarcopenia in the elderly (American College of Sports 2009; Garber et al 2011). Another well-established benefit of RT is the prevention of abdominal and total fat gain and increases in markers of both inflammation and metabolic risk factors (American College of Sports 2009;Garber et al 2011;Lera Orsatti et al 2014;Maesta et al 2007;Orsatti et al 2010a;Phillips et al 2012;Senechal et al 2012). However, it has been established that a higher volume (amount) of exercise (or higher energy expenditure) reduces abdominal fat and metabolic risk factors in overweight and obese people (American College of Sports 2009;Friedenreich et al 2015;Garber et al 2011;Lera Orsatti et al 2014;Nimmo et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unclear whether RT represents a good strategy to prevent muscle loss during CR (which includes dietary protein restriction). Some studies have reported no change or even reduced LBM following CR when RT is included in the intervention program [ 7 , 14 , 15 , 16 , 17 , 18 ]. On the other hand, randomized clinical trials (RCT) comparing CR with and without RT have shown the preservation of LBM with RT [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%